2019
DOI: 10.21873/anticanres.13320
|View full text |Cite
|
Sign up to set email alerts
|

Zone Formation of Lymphocyte Infiltration at the Invasive Front Results in the Prolonged Survival of Individuals With Endometrial Serous Carcinoma and Endometrioid Carcinoma With Serous Component

Abstract: Background/Aim: This study aimed to evaluate the clinical significance of lymphocyte infiltration (LI) for patients with endometrial serous carcinoma and those with endometrioid carcinoma including serous component. Patients and Methods: Patients who underwent surgery at our hospital between 1990 and 2013 were identified. LI was classified into strong LI, defined as a continuous thick zone of LI, and weak LI, defined as the lack of zone or scattered small foci of LI at the invasive front. Results: Out of a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Several reports have revealed an important association between TILs and the prognosis of endometrioid carcinoma (8)(9)(10)(11)(12)(22)(23)(24). These studies demonstrated that cluster of differentiation (CD)3 + T-lymphocytes, CD8 + T-lymphocytes, CD45R0 + T-lymphocytes, and CD8 + /forkhead box protein (FOXP)3 + ratios were associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have revealed an important association between TILs and the prognosis of endometrioid carcinoma (8)(9)(10)(11)(12)(22)(23)(24). These studies demonstrated that cluster of differentiation (CD)3 + T-lymphocytes, CD8 + T-lymphocytes, CD45R0 + T-lymphocytes, and CD8 + /forkhead box protein (FOXP)3 + ratios were associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies evaluated TILs in the tumor stroma (8,9,(22)(23)(24). However, our earlier reports focused on TILs at the invasive front and indicated their importance in prognosis (10,11). Recently, Pagès et al suggested that the presence of CD3 + as well as cytotoxic CD8 + T-cells in the tumor and in the invasive margin constitute prognostic factors for patients with colon cancer (27).…”
Section: Trafficking Of T-cells To Tumors Infiltration Of T-cells Int...mentioning
confidence: 98%
See 1 more Smart Citation